Navigating the potassium dilemma: a qualitative study of nephrologists’ strategies for renin–angiotensin–aldosterone system inhibitor preservation and hyperkalaemia management in Spain - Nicolas Gimenez-Stamminger; Ceu Mateus; Thomas Mason; Andrew Harding (PLoS ONE, 2026)
Background Hyperkalaemia is a common complication among patients with predialysis chronic kidney disease (CKD) and a leading reason for modifying or discontinuing renin–angiotensin–aldosterone system inhibitor (RAASi) therapy despite its proven cardiorenal benefits. Although newer potassium binders may improve potassium control while enabling RAASi use, real clinical practice remains poorly characterised. This study explored how nephrologists in Spain manage hyperkalaemia in patients with predialysis CKD (stages 3–5), with particular emphasis on RAASi continuation. Methods Semi-structured interviews were conducted with 12 practising nephrologists across Spain who routinely manage hyperkalaemia in patients with predialysis CKD. Interviews were transcribed verbatim and analysed using ATLAS.ti. A codebook-based thematic analysis was performed, with codes iteratively refined into 15 sub-themes and grouped into five overarching themes. Results Five themes were identified: (1) hyperkalaemia was managed using a structured clinical algorithm incorporating dietary, metabolic, diuretic, and pharmacological strategies, to preserve RAASi therapy where possible; (2) newer potassium binders (patiromer and sodium zirconium cyclosilicate) were viewed as effective and better tolerated than traditional resins, supporting greater RAASi continuity; (3) system-level barriers, including visado requirements, regional formulary variation, and fragmented communication across specialties, limited timely use of newer binders were perceived to contribute to RAASi discontinuation; (4) patient engagement, underpinned by clear communication, trust, and nursing-led education, facilitated adherence, although clinician-level nutrition expertise varied; and (5) hyperkalaemia management affected patients’ daily functioning and emotional well-being, yet formal assessment of health-related quality of life (HRQoL) was infrequent. Conclusions Nephrologists in Spain prioritised preservation of RAASi therapy when managing hyperkalaemia in predialysis CKD. Although newer potassium binders supported this objective, their use was limited by access and care coordination challenges. Streamlined access pathways, improved multidisciplinary communication, and routine HRQoL assessments may enable more patient-centred and guideline-concordant care. These implications reflect qualitative clinician perspectives rather than evidence of clinical or economic effectiveness.